The profile of construction contract termination cases - 254029 Roslinda Rosly; Norazam Othman, supervisor; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2009